2012
DOI: 10.4103/0976-237x.107448
|View full text |Cite
|
Sign up to set email alerts
|

Autogenous bonding of tooth fragment retained in lower lip after trauma

Abstract: In cases of trauma, dental fragments occasionally penetrate into the soft-tissues and may cause severe complications, if neglected. Clinical and radiographic examinations can provide a diagnosis and help in the surgical removal of any dental fragment embedded in soft-tissue. This case report concerns an 8-year-old boy who was diagnosed with a fragment of a fractured permanent central incisor crown located in the lower lip. The patient was seen initially at a general hospital, where the dental fragment went unn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…[ 1 23 ] Among these, in most of the reported cases (16 out of 24 case reports), the lower lip was the most common site for the embedded incisor fragment. [ 1 , 3 , 4 , 9 , 11 17 , 19 , 20 , 22 , 23 ] However, Kalra et al ,[ 10 ] Cubukcu et al ,[ 18 ] and Agarwal et al [ 2 ] reported cases with tooth fragments embedded in the upper lip. McDonnell and McKiernan (in 1986)[ 7 ] and Hill et al [ 6 ] published case reports of tooth fragments embedded in the tongue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 23 ] Among these, in most of the reported cases (16 out of 24 case reports), the lower lip was the most common site for the embedded incisor fragment. [ 1 , 3 , 4 , 9 , 11 17 , 19 , 20 , 22 , 23 ] However, Kalra et al ,[ 10 ] Cubukcu et al ,[ 18 ] and Agarwal et al [ 2 ] reported cases with tooth fragments embedded in the upper lip. McDonnell and McKiernan (in 1986)[ 7 ] and Hill et al [ 6 ] published case reports of tooth fragments embedded in the tongue.…”
Section: Discussionmentioning
confidence: 99%
“…A literature search revealed 6 cases with reattachment procedures using the tooth retrieved from the soft tissues in addition to the long-term results. [ 1 , 3 , 13 , 15 , 16 , 19 ]…”
Section: Discussionmentioning
confidence: 99%